The role of rumination in posttraumatic stress disorder and posttraumatic growth among adolescents after the wenchuan earthquake - Wu, Xinchun; Zhou, Xiao; Wu, Yufei; An, Yuanyuan (Frontiers in Psychology, 2015)
Three hundred and seventy-six middle school students in Wenchuan County were assessed three and one-half years after the Wenchuan earthquake to examine the effects of rumination on posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG). The results revealed that recent intrusive ruminations partly mediated the relationship between intrusive rumination soon after the earthquake with PTSD but not with PTG. Recent deliberate rumination partly mediated the relationship between intrusive rumination soon after the earthquake and PTG but not PTSD. Moreover, recent deliberate rumination also partly mediated the relationship between recent intrusive rumination with PTG but not with PTSD. Overall, intrusive rumination soon after the earthquake had an effect on PTSD but not on PTG through recent intrusive rumination and affected PTG but not PTSD through deliberate recent rumination. Furthermore, intrusive rumination soon after the earthquake affected PTG but not PTSD by recent deliberate rumination following recent intrusive rumination. More importantly, the present study also found that PTSD exhibited no relation to PTG. These results suggest that PTSD and PTG are influenced by different mechanisms, which further indicates that PTSD and PTG represent two separate dimensions of experience after adversity.